Hult prize event at BRAC University - Nidhi, Mahejabeen Hossain (The Daily Star, 2014)
The event was in partnership with Clinton Global Initiative. It was sponsored by Nitol Motors Limited and powered by Radio Foorti. Global Affairs Forum of BRAC University was Logistics Partner, and The Daily Star was Media Partner.